Embedding of fine features in multi-scale electromagnetic models - Biwojno, Konrad P. (2006)
Modelling detailed electromagnetic interactions in Electromagnetic Compatibility predictions is an extremely demanding task, made more difficult by the increasing complexity of modem engineering problems. Over the last decade major innovations in numerical models and methods have been introduced to reduce demands on computational resources or render the simulations of large systems containing a diverse range of physical features possible.